Strain Measuring of Composite Grid Using Digital Image Correlation - Chhoung Lim; Yeongseok Jeong; Suchart Limkantanyu; Minho Kwon (Advances in Materials Science and Engineering)
Digital Image Correlation (DIC) is a new advanced technique for measuring the deformation of a specimen using high-resolution images. It has been used by numerous researchers since it can measure the deformation of specimens without interference because it is contactless. Moreover, the DIC technique can be applied to any materials to which normal measuring equipment is difficult to attach such as Fiber-Reinforced Polymer (FRP) grid in this paper, undulated and small surfaces. The DIC technique is easy to set up and provides reliable results compared to conventional equipment like a strain gauge. Although it is good, its associated equipment is too expensive to be readily affordable. Hence, this paper uses an open-source DIC program called Ncorr that works in MATLAB to analyze deformations of six FRP grids from direct tensile tests by comparing their results to the results from a strain gauge. Young’s modulus—calculated from ASTM 3039, ACI 440-3R-04, and regression analysis—of each specimen will be used for comparison. The results show that the difference between Young’s modulus from DIC and strain gauge is <5% if the stress–strain graph of data from the strain gauge is perfectly linear without straying.